UKRAINE IN THE CONTEXT OF EUROPEAN COLLECTIVE SECURITY: ROLES OF STATES AND INTERNATIONAL ORGANIZATIONS - KLISH, Andriy (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Annotation. The proposed article explores the concepts of balance of power in international relations, its historical development, and contemporary application. The author examines theoretical approaches to the balance of power, their advantages and disadvantages, as well as practical examples of power balancing between states in Europe and the world from the 20th to the early 21st century. Special attention is given to the roles of NATO and the United States, as well as the international alliance contributing to collective security, and the challenges posed by Russia under the leadership of Putin to the international order.